Japan and Its Complex Position in the Nuclear Age: Moving from Vagueness to Concreteness - Wakana Mukai (Journal for Peace and Nuclear Disarmament, 2025)
Although Japan has experienced the tragedy of the use of nuclear weapons during warfare in 1945, it stands as a prominent nation that has adopted a substantial reliance on nuclear weapons in its security strategy. What, then, does it mean for Japan to promote nuclear disarmament? This article sorts out the positives and negatives for Japan regarding prioritizing or deprioritizing nuclear deterrence and nuclear disarmament as part of its nuclear policy and reconfirms that whichever policy it prioritizes, there will always be a possibility of conflicting interests. To this end, Japan must take specific actions/steps to demonstrate its commitment to nuclear disarmament, including supporting the actual movement and policy of nuclear powers toward nuclear disarmament, which would contribute to reducing the value of nuclear weapons. This article looks at a case in which Japan showed opposition in a potential shift of nuclear policy of the United States toward a no first use policy and suggests that Japan’s actions may hinder the creation of an environment conducive to nuclear disarmament, thereby undermining the country’s commitment to this cause.